The advent of the 'Festivore' an exploration of South African audience attendance in the performing arts at the National Arts Festival - Antrobus, Richard Roy (Rhodes University, Faculty of Humanities, Department of Drama, 2010)
In South Africa, the performing arts have contributed to enhancing national identity and distinctiveness despite coming up against weak legislation, policy and infrastructure to support their growth and proliferation (Fredericks, 2005: 9). Coupled with a decline in both government and consumer support and the contradictory disparity between valuing the arts and the funding of the arts, theatre companies can no longer rely on the comfort of external subsidies and financial support. In order to be economically viable and sustainable to ensure their survival, there is an increasing demand for theatre companies to look to novel ways of increasing audience demand for theatre and improving audience attendance. However, instead of risking artistic integrity and the performance product to satisfy the market, this research suggests that promotion and development of theatre at arts festivals provides a platform to access a wider theatre-going public, which therefore facilitates a change in the market focus toward appreciation of the product (production). It explores leading arguments pertaining to the attendance of arts and cultural events, namely, Peterson and Simkus (1992), later updated by Peterson"Ÿs (2005)omnivore-univore"Ÿ argument. The argument purports cultural consumption as binary in nature: either significant and diverse or limited, if not absent altogether. Supported by a number of case-studies, including Chan and Goldthorpe (2005) and Montgomery and Robinson (2008) and Snowball et al. (2009), the investigation challenges Bourdieu"Ÿs (1984) theory on cultural distinction as well as the homology and individualisation argument. In determining the factors that influence cultural taste and consumer behaviour, including motivators and inhibitors of attendance and a predominant emphasis on audience risk and information asymmetry, the research was placed in a local context, providing an overview of the socio-economic theatre environment in South Africa. It investigated the nature, structure and impact of local festivals (as events) in changing audience demand and theatre attendance. With specific reference to the South African National Arts Festival (NAF) the research notes the effects of Hauptfleisch"Ÿs eventification"Ÿ phenomenon on univore attenders and therefore expands the omnivore-univore theory to include a new breed of attender: the "Festivore" . A case study explored the "Festivore" hypothesis through empirical research, surveys and face-to-face qualitative interviews and on-seat questionnaire responses by festival attenders. Personal interviews and communication was also carried out with leading experts in the field. The data was then analysed using SPSS 13 electronic statistical analysis programme to determine the socio-demographics and the factors that affect theatre attendance of existing, as well as potential target, theatre audiences at the National Arts Festival The study concluded that South African theatre attenders are generally omnivorous consumers and that, more importantly, there seems to be a shift towards festivorous"Ÿ consumption. Furthermore, evidence supports the development and proliferation of festivals as a means not only to support and promote the arts in South Africa but, more importantly, to generate new theatre audiences and entrench theatre attendance into South African culture.
Keywords: Standard Bank National Arts Festival -- Economic aspects; Arts -- Economic aspects; Performing arts festivals -- Economic aspects -- South Africa -- Grahamstown; Arts -- South Africa -- Economic aspects; Arts -- South Africa -- Finance; Arts -- South Africa -- Political aspects; Arts audiences -- South Africa